PENGARUH PENERAPAN PROJECT BASED LEARNING (PJBL) DALAM PEMBELAJARAN SOSIOLOGI SEBAGAI UPAYA MENINGKATKAN KREATIVITAS SISWA (STUDI KASUS SISWA FASE E 1 DI SMA N 1 SUTERA) - Yuka Fitri Yanti; Yanti Sri Wahyuni; Erningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the fact that the project based learning model is not yet effective, student learning creativity is still low. One effort to overcome this problem is to apply the project based learning model in the sociology learning process. The aim of this research is to determine the effect of implementing project based learning in sociology learning as an effort to increase the creativity of Phase E 1 students at SMA N 1 Sutera. The theory used in this research is the behaviorist theory put forward by Gagne. The type of research used is quantitative because the data obtained is in the form of numbers. with Quasi-experimental research type. The population in this study were class X students of SMA N 1 Sutera with a sample size of 36 people. Sampling used purposive sampling technique. The instrument used for this research was an observation sheet. The data analysis technique in research is by using the T Test. Based on the results of research that has been carried out using the t test statistic, tcount = 21.13. Then t table with dk = n-k-1, dk = 36-1-1 = 34 at a significance level of 5% (0.05), then from the t distribution table the value of t table = 2.032 is obtained. So the result is 21.13 > 2.032 so that Ha is accepted and Ho is rejected. The result of hypothesis testing is that Ha is accepted, meaning that there is an influence of the application of the project based learning model in sociology learning as an effort to increase creativity (case study of Phase E1 students at SMA N 1 Sutera).